2015
DOI: 10.1179/1432891714z.0000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and frost resistance properties of high air content hydraulic concrete

Abstract: The frost resistance of hydraulic concrete is evaluated under −17°C freezing temperature according to the Chinese standards. However, the freezing-thawing condition is usually less than −17°C because of the broad distribution of water conservancy project in China. Therefore, the freezing-thawing cycle experiment of high frost resistance design level concrete with air content above 5·5% was conducted, and −17, −30 and −40°C freezing temperatures were adopted during the test. The mechanics and frost resistance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Many researches have shown that the mechanical properties of concrete after water saturation are quite different from those at the dry state 7 , 8 . At present, the researches on the mechanical properties of concrete after water saturation are mainly limited to quasi-static cases, and there are still some deficiencies among the researches of its dynamic mechanical properties 9 11 . Rossi et al studied the effect of free water on the properties of concrete under tensile stress, and explained the change mechanism of mechanical properties of concrete after water saturation.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have shown that the mechanical properties of concrete after water saturation are quite different from those at the dry state 7 , 8 . At present, the researches on the mechanical properties of concrete after water saturation are mainly limited to quasi-static cases, and there are still some deficiencies among the researches of its dynamic mechanical properties 9 11 . Rossi et al studied the effect of free water on the properties of concrete under tensile stress, and explained the change mechanism of mechanical properties of concrete after water saturation.…”
Section: Introductionmentioning
confidence: 99%